BUNUK: PENGETAHUAN DAN PRAKTEK ATONI-METO DALAM TATA KELOLA HUTAN - Yohanes Victor Lasi Usbobo (Program Studi Filsafat Agama Universitas Katolik Widya Mandira Kupang, 2019)
The implementation of todays forest management that based on formal-scientific knowledge and technical knowledge seems to fail to protect the forest from deforestation and the environmental damage. Decolonialisation of western knowledge could give an opportunity to identify and find the knowledge and practices of indigenous people in sustainable forest management. Forest management based on the indigenous knowledge and practices is believed easy to be accepted by the indigenous community due to the knowledge and practice is known and ‘lived’ by them. The Atoni Pah Meto from West Timor has their own customary law in forest management that is knows as Bunuk. In the installation of Bunuk, there is a concencus among the community members to protect and preserve the forest through the vow to the supreme one, the ruler of the earth and the ancestors, thus, bunuk is becoming a le’u (sacred). Thus, the Atoni Meto will not break the bunuk due to the secredness. Adapting the bunuk to the modern forest management in the Atoni Meto areas could be one of the best options in protecting and preserving the forest.